The Conundrum of Taiwan Issue: Implications on World Politics - Zahid Yaseen; Muhammad Muzaffar; Khadija Shahbaz (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This qualitative study examines the complex dynamics of the Taiwan-China dispute and its wide-ranging effects on the world economy and politics. The Taiwan dispute, which has its roots in the aftermath of the Chinese Civil War, has gained prominence in international relations, and the US’s strong involvement in it directly challenges China, the most populous country on earth and a rising global power. This study attempts to offer a nuanced understanding of the complex aspects of the Taiwan-China dispute by utilizing a qualitative methodology that combines in-depth interviews, content analysis of diplomatic discourse, and historical record inspection. The results emphasize that current geopolitical dynamics need to be reevaluated and that diplomatic dialogue is the best means of achieving peaceful resolutions. Moreover, the research underscores the possible worldwide ramifications of intensified measures, specifically concerning the United States and China. This study advances our understanding of how geopolitical tensions, sovereignty concerns, and their effects on the world economy interact.